ANALISA LOGAM BERAT DALAM AIR MINUM ISI ULANG (AMIU) YANG BEREDAR DI KOTA BATAM - Fitrah Amelia (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2021)
The purpose of this study was to analyze and determine the levels of metal content contained in refill drinking water circulating in the city of Batam. To achieve this goal, research activities were carried out 2 times sampling at 6 refill drinking water depots in Batam City. The research was conducted at the chemical laboratory of the University of Riau Islands and analysis of metal contamination was carried out by analysts using the ICP-MS method at the Indonesian Surveyor Laboratory in Batam using the services of an analyst. The methods used in this study include descriptive methods to determine sampling techniques, and laboratory examinations. From the results obtained, it can be concluded that the levels of Cu, Cd, and Pb metals in the 6 refill drinking water depots are below the standard that has been set based on SNI and Minister of Health regulations No. 492/Menkes/Per/IV/2010. So that the refill drinking water is fit for consumption.